Employment opportunities and pre-marital births in Britain - John Ermisch (University of Essex, Institute for Social and Economic Research (ISER), 2000)
In 1999, nearly two-fifths of births in Britain were outside marriage. This study estimates the impact of employment opportunities in the local labour market on the probability that a childless never married woman has a birth outside marriage. It uses the unemployment rate in the travel-to-work area in which the woman lives as the indicator of employment opportunities. The estimates indicate poorer employment opportunities increase the pre-marital first birth rate and discourage union formation.
Keywords: 330